SMARTPHONES AND EFFECTS ON CHILDREN'S SPEECH DELAYS - Rinaldi, Annisa Namira; Utami, Safia; Tanzielin N, Silmi Kaffah; Utami, Widya Putri (Pusat Penerbitan Universitas (P2U) Unisba, 2023)
A smartphone is a telecommunications device with various features that make long-term smartphone users, including children, feel at home. on the one hand, the inclusion of smartphones in technological progress. On the other hand, children usually prefer to play with gadgets and smartphones rather than traditional games and physical games. Children's language development is affected by this. Community members use an arbitrary system of spoken symbols, based on a shared culture, to communicate and interact with one another. Children with language development delays often try to communicate through body language so that others can understand what they are saying. The purpose of this study was to investigate the impact of smartphones on children with a diagnosis of speech delay. The problem situation is revealed as it is through the use of qualitative research methods in this study. Interviews and observations were used to gather information. The respondents of this study were mothers of seven-year-old twins who were diagnosed with speech delays. The study found that the amount of speech delay time children spent using smartphones impacted their language development, leading to therapy being applied to areas where there was no progress.